POTENSI EKOSISTEM HUTAN MANGROVE DI BLOK PEMANFAATAN TAMAN WISATA ALAM PULAU KEMBANG PROVINSI KALIMANTAN SELATAN - , Nikmat Hakim Pasaribu, Dra. Erny Poedjirahajoe, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Information about the potency of mangrove resources are needed for management planning and utilization patterns in mangrove forests. In this study the placement of plots measuring carried out systematically. The environmental of habitat data collection is done by direct measurement, The collection of vegetation data using the combination line transect with a square line method, mamals data using the line transect method with right- left lane width of 20 m and 40 m spacing between lines, and attractions data are formulated based on the potency of mangrove forest ecosystem. The results showed that the environmental of habitat in the Block Utilization of Nature Recreation Park (BU NRP) of Kembang Island what still supports the growth of the mangrove forests. The measured parameters of environmental of habitat of each in BU-1 and BU-2 include the soil factors (pH 6.1 and 6.5